Association of various morpho-phenological traits with yield among various rice (Oryza sativa L.) genotypes - M.H.V. BHAVE, GODAWARI S. PAWAR, V. PADMA, D. SUBRAHMANYAM S. SUDHEER KUMAR and (The Journal of Research, PJTSAU, 2017)
The objective of the study was to evaluate different varieties of rice for their growth and yield characteristics. An experiment was conducted during kharif 2013 and kharif 2014 at ICAR-Indian Institute of Rice Research, Rajendranagar, Hyderabad. Fourty three genotypes from different groups were evaluated in a randomized block design (RBD) with three replications. Data on various growth and yield parameters reveled that the parameters were significantly differed among the genotypes. Evaluation of fourty three rice genotypes from different groups showed significant differences among the genotypes. Positive and significant correlation of yield was found with total dry matter per hill (0.89), tillers per plant (0.58, days to flowering (0.40) and days to maturity (0.35). Grain yield was positively associated with plant height (0.07), percent filling grains (0.17) and 1000 seed weight (0.07). It indicated that grain yield can be increased whenever there is an increase in characters that showed positive and significant association with grain yield. Hence due weightage should be given to these characters during selection for future crop improvement programme.